[PP.20.15] IMPEDANCE CARDIOGRAPHY BETTER CHARACTERIZES HEMODYNAMIC ALTERATIONS RELATED WITH LEFT VENTRICULAR DIASTOLIC FUNCTION IN HYPERTENSIVE MEN THAN WOMEN. (September 2016) - Stanczyk, A.; Krzesinski, P.; Gielerak, G.; Uzieblo-Zyczkowska, B.; Piotrowicz, K.; Skrobowski, A.
Abstract : Objective: Left ventricular diastolic dysfunction (LVDdf) and arterial stiffness are associated with increased mortality in patients with arterial hypertension (AH). Better understanding of the hemodynamic alterations related to LVDdf in men and women demands the assessment of ventricular-vascular interrelations. Impedance cardiography (ICG), a noninvasive method of hemodynamic evaluation, appeared to have diagnostic potential in this area. The aim of the study was to evaluate the relation between LVDdf and hemodynamic profile assessed by ICG in terms of sex and to identify the ICG parameters clinically useful as determinants of LVDdf. Design and method: 209 patients with unmedicated AH were enrolled (males: 146; mean age: 46.0 years). Two-dimensional echocardiography was performed to diagnose LVDdf and the following values were considered abnormal: mitral septal annulus early diastolic velocity (e') <8 cm/s; left atrium >40 mm for men and >38 mm for women; mitral flow early and late phase ratio (E/A) <0.8; phase E deceleration time (EdecT) >200 ms; isovolumic relaxation time (IVRT) >=100ms; E/e' ratio >8. ICG measurements were performed using the Niccomo™ (Medis, Germany) with evaluation: 1/ indices of left ventricular performance: stroke index (SI), acceleration time index (ACI), velocity index (VI), Heather index (HI) and 2/ arterial stiffness: total arterial compliance (TAC) and systemic vascular resistance index (SVRI). Results: Significant correlations between clinical/hemodynamic features and echocardiographic indices of the LVDdf were observed only in males (Table 1), the most relevant for: age vs E/A (−0.45; p < 0.001), VI vs e' (0.30; p < 0.001), VI vs E/A (0.30; p < 0.001), and SVRI vs e' (−0.28; p < 0.001). ROC curve analysis for selected variables related to LVDdf showed that only VI and HI cut-offs characterized with acceptable likelihood ratio (LR >2.0). Univariate analysis revealed significance in determining LVDdf for the following ICG variables: VI>40.1[1000*Ohm/s], HI>11.4[Ohm*s 2 ], ACI>62.3[100*Ohm/s 2 ], SI>48.7[ml/m 2 ] and SVRI>2200[dyn*s*m 2 /cm 5 ]. At multivariate regression models (Table 2) only VI, HI and ACI revealed to be independent of age and BMI predictors of LVDdf (ORs: 2.55; 1.98; 1.84; respectively). Conclusions: Impedance cardiography is useful in the evaluation of ventricular-vascular interrelations related to LVDdf in young and middle-aged hypertensive men. Figure. No caption available.